2023
DOI: 10.9734/ajraf/2023/v9i1191
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Biochar and Organic Soil Amendments on Seedling Development of Annona muricata. Linn

Abstract: The importance of appropriate growth media for propagation of Annona muricata seedlings cannot be over emphasized. An experiment was conducted to investigate the effects of biochar and organic soil amendments on seedling development of Annona muricata using different potting media. The treatments were Control; Topsoil only (T0), Mineralized goat dung (T1), Mineralized saw dust (T2), Mineralized poultry dropping (T3) and Mineralized biochar (T4). The experiment was laid out in Completely Randomized Design (CRD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
3
0
2
Order By: Relevance
“…In Awka, Anambra State, Anozie et al [171] examined the influence of different growth media on the initial growth of Annona muricata L. seedlings. The study's findings indicated that goat dung, sawdust, and chicken droppings were followed by topsoil amended with biochar (BC) derived from Tectona grandis L.f., Irvingia gabonensis (Aubry-LeComte er O'Rorke) Bail, and Gmelina arborea Roxb.…”
Section: A Case Study Of Recent Studies Of Biochar In Nigeriamentioning
confidence: 99%
See 2 more Smart Citations
“…In Awka, Anambra State, Anozie et al [171] examined the influence of different growth media on the initial growth of Annona muricata L. seedlings. The study's findings indicated that goat dung, sawdust, and chicken droppings were followed by topsoil amended with biochar (BC) derived from Tectona grandis L.f., Irvingia gabonensis (Aubry-LeComte er O'Rorke) Bail, and Gmelina arborea Roxb.…”
Section: A Case Study Of Recent Studies Of Biochar In Nigeriamentioning
confidence: 99%
“…Studies on various crops such as Annona muricata [171], cowpea [176], sesame [177], okra [180], tomato [42], and ginger [187] demonstrated the positive effects of BC on growth and yield. These findings suggest that BC application benefits a wide range of crops, making it a versatile soil-amendment option.…”
Section: A Case Study Of Recent Studies Of Biochar In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…Ainda segundo esses autores, a Annona muricata L. apresenta ainda atividade antiprotozoária, antioxidante, antiviral, anticâncer, antiúlcera, anti-inflamatória e hipotensora. Anozie et al (2023) descrevem a Annona muricata como uma planta de folhas brilhantes e robustas, apresentando flores grandes, sozinhas ou em grupo de até três flores. Santos et al (2023) ressaltam que a graviola, como a Annona muricata.…”
Section: /16unclassified
“…é conhecida, pertence à família Annonaceae, que, segundo Pinto & Silva (1995), compreende 75 gêneros e 600 espécies, das quais apenas Annona e mais três gêneros possuem frutos aptos ao consumo. Anozie et al (2023) ressaltam, no entanto, que essa espécie está classificada com risco de extinção devido a ação antrópica, pragas e doenças.…”
Section: /16unclassified